Classification of eye diseases in fundus images using Convolutional Neural Network (CNN) method with EfficientNet architecture - Zhafeni Arif; R. Yunendah Nur Fu’adah; Syamsul Rizal; Divo Ilhamdi (IICET (Indonesian Institute for Counseling, Education and Therapy), 2023)
This research is designed to classify eye disease conditions into three classes, namely normal, cataract, and glaucoma using a system. The system will use Convolutional Neural Network (CNN) with EfficientNet architecture. The EfficientNet that will be used is EfficientNet-B0. The dataset in this paper is obtained from Kaggle totaling 300 images. From this data, augmentation is carried out so that 3.600 images are obtained consisting of